Risk factors and epidemiology of pediatric ventriculoperitoneal shunt infection. Issue 12 (10th December 2018) - Erps, Amir; Roth, Jonathan; Constantini, Shlomi; Lerner‐Geva, Liat; Grisaru‐Soen, Galia
Abstract: Background: The aim of this study was to identify independent risk factors for cerebrospinal fluid shunt infection. Methods: The medical records of all patients aged 0–18 years who underwent shunt‐related surgery for the treatment of hydrocephalus at the present institution between January 1996 and December 2015 were reviewed. For each case, two randomly selected controls with no shunt infection, matched for year of surgery, were chosen. Demographic clinical and microbiological data were abstracted. Results: A total of 1, 570 shunt‐related procedures met the inclusion criteria, yielding 68 infections (in 63 patients). The control group consisted of 132 infection‐free patients. The average annual infection rate was 4.2% cases per year. The median time between shunt procedures to infection was 19 days (range, 1–2, 181). On multivariate analysis, risk factors associated with increased risk for developing an infection included a history of two or more previous revisions (OR, 4.8; 95%CI: 1.5–15.9); and age <5 years (OR, 4.5; 95%CI 1.5–13.4). A neoplastic etiology for hydrocephalus was found to be a protective factor for shunt infection ( P = 0.001). Conclusions: A history of shunt revision was the most significant risk factor in the development of subsequent shunt infection. Age >5 years was a protective factor. Future efforts should focus on modalities to optimize revision procedures and reduce the risk of subsequent infection.